Climate change has increased household electricity Consumption——An adaptive behavioral perspective - Jieyu Li; Kun He (China Economic Quarterly International)
Using the panel data of 244 cities from 2011 to 2020, this paper constructs temperature deviation indicators and evaluates the effects of climate change on electricity consumption from an adaptive behavioral perspective. This paper finds that cooling degree days (CDD) push up electricity consumption, among which the purchase and use of air conditioners contribute about 58.7 ​% – 78.7 ​%. Heterogeneity analysis reveals that extreme temperature, humidity, and income strengthen the response of electricity consumption and air conditioner purchase to CDD. Technological advancements that reduce air conditioning energy consumption can only partially alleviate the positive impact of air conditioning usage duration on household electricity consumption.